The Influence of Blue Ocean Strategy on Organizational Performance - Rahman, Md. Habibur; Choudhury, Sabbrina (Global Disclosure of Economics and Business, 2019)
The study deals with the blue ocean strategy (BOS) that offers users a framework for making uncontested market space and diverts the outlooks from the existing competition to the creation of innovative value and demand. The purpose of the study is to determine the influence of BOS on organizational performance. In this study, we systematically examine previous research on these topics of BOS. The findings show that there is a significant contribution of BOS to the enhancement of organizational performance. The study recommends that the policymakers should perform a critical analysis of BOS before implementation to see its suitability in the desired organization. Additionally, we identify future research areas that provide scholars opportunities to push theoretical boundaries and offer further insights into the study of BOS. JEL Classification Codes: M31, L25